Review and Resolution of Administrative Cases in Automated Mode in Light of the Law “On Administrative Procedure” - Khliborob, Natalia (Problems of legality, 2023)
The relevance of the topic is driven by the rapid development of digital technologies and the implementation of automated systems in various aspects of life, including the administrative sphere. The aim of the article is to investigate and analyze the procedure for considering and resolving administrative cases in automatic mode according to the Law of Ukraine "On Administrative Procedure." Achieving this goal became possible through the use of a comprehensive set of scientific methods, including legislative analysis, comparative analysis of foreign experience, and legal analysis of the provisions of the law. The key provisions of the Law of Ukraine "On Administrative Procedure" related to the automatic mode of considering administrative cases have been examined. It is noted that the law requires amendments to specify the use of automation, establish legal frameworks for this method of resolving administrative cases, and provide clear legal regulation of aspects such as the legal stability of automatically adopted administrative acts, rights, and obligations of citizens in this context. It is established that defining the responsibilities of administrative bodies in providing information and clarification to individuals about the automatic mode is a crucial aspect for safeguarding citizens’ rights. Emphasis is placed on the necessity for further legislative improvements to consider aspects of legal definiteness, protection of individuals’ rights, and the neutrality of decisions, ensuring fairness in the resolution of administrative cases in automatic mode. Conclusions and recommendations for further improvements in legislation and the practice of handling administrative cases in automatic mode have been formulated based on the conducted research. Prospects for further research include an extended analysis of the effectiveness of implementing automated systems in the field of public administration.